A Genetic Screen for Human Genes Suppressing FUS Induced Toxicity in Yeast. Issue 6 (1st June 2020) - Hayden, Elliott; Chen, Shuzhen; Chumley, Abagail; Xia, Chenyi; Zhong, Quan; Ju, Shulin
Abstract: FUS is a nucleic acid binding protein that, when mutated, cause a subset of familial amyotrophic lateral sclerosis (ALS). Expression of FUS in yeast recapitulates several pathological features of the disease-causing mutant proteins, including nuclear to cytoplasmic translocation, formation of cytoplasmic inclusions, and cytotoxicity. Genetic screens using the yeast model of FUS have identified yeast genes and their corresponding human homologs suppressing FUS induced toxicity in yeast, neurons and animal models. To expand the search for human suppressor genes of FUS induced toxicity, we carried out a genome-scale genetic screen using a newly constructed library containing 13570 human genes cloned in an inducible yeast-expression vector. Through multiple rounds of verification, we found 37 human genes that, when overexpressed, suppress FUS induced toxicity in yeast. Human genes with DNA or RNA binding functions are overrepresented among the identified suppressor genes, supporting that perturbations of RNA metabolism is a key underlying mechanism of FUS toxicity.